Design of Oil Palm frond Mechanically Cutlery - Arsenius Ardinata Tarigan; Saipul Bahri Daulay; Achwil Putra Munir (Universitas Sumatera Utara, 2013)
Palm frond cutting is still done manually, where the operator has limitations in cutting the frond. He must be really experienced and have high levels of accuracy and the work capacity is relatively limited. Therefore a mechanical cutting equipment was made. This study was conducted in May to September 2013 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, Medan, with a literature study, making and test the equipment and observation of parameters. The parameters measured were the equipment capacity, economic analysis, break-even point, the internal rate of return, and net present value. The results demonstrated that device capacity was 142.78 frond / h, economic analysis was Rp 55.873 / frond, break event was 71577.091 point / year, the internal rate of return was 40.2547 % and the equipment was deserved to be made. Keywords : agricultural equipment and machinery, cutter, oil palm frond.